1991
DOI: 10.1002/app.1991.070420507
|View full text |Cite
|
Sign up to set email alerts
|

Solution and emulsion polymerization with partially neutralized methacrylic acid

Abstract: SYNOPSISPolymerizations of partially neutralized methacrylic acid ( MAA) were performed in both solution and emulsion systems. Polymerizations of MAA in solution were performed at an overall degree of neutralization ranging between 0 and 1. The rate of polymerization of the acid is found to decrease as the degree of neutralization increases due to increased electrostatic repulsion of the dissociated acid species (anions). The degree of neutralization of the unreacted monomer increases as the conversion increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…Carboxylated seed latexes were also used by Coen et al 30 to study the influence of pH on the emulsion polymerization of S. Poly(acrylic acid) as stabilizer played a crucial role in the mechanism of the polymerization, which is probably also the case in the work of Shoaf and Poehlein. 9,10 Our systems actually describe the carboxylation process of polystyrene latexes and in this context the limited effect of pH on the polymerization rate is plausible. n increases with the particle diameter which is in agreement with the emulsion-polymerization theory reported by Ugelstad et al 31 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxylated seed latexes were also used by Coen et al 30 to study the influence of pH on the emulsion polymerization of S. Poly(acrylic acid) as stabilizer played a crucial role in the mechanism of the polymerization, which is probably also the case in the work of Shoaf and Poehlein. 9,10 Our systems actually describe the carboxylation process of polystyrene latexes and in this context the limited effect of pH on the polymerization rate is plausible. n increases with the particle diameter which is in agreement with the emulsion-polymerization theory reported by Ugelstad et al 31 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the MAA monomer is soluble in water and has a dissociation constant of pK a = 4.36, the partitioning of MAA between the aqueous phase and the particles depends on the pH of the reaction environment [12]. Increasing the pH led to higher concentrations of the dissociated form of the acid, and the quantity of MAA found in the organic phase decreased accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the increase in the hydrophilicity of the oligomeric radicals formed in the aqueous phase decreased the driving force for the radicals to penetrate into the hydrophobic particulate phase. Because of the MAA homopolymer at the surface of the polymer particles, the potential barrier for penetration of oligomeric radicals decreased the rate of polymerization at higher pH [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…polymerization rate per particle or equivalently average number of propagating radicals per particle is also affected by the presences of carboxylic acid monomers. 3,[5][6][7][8] Shoaf and Poehlein 7,8 developed a model that describes the kinetics of particle growth in seeded emulsion copolymerization of styrene with acrylic and methacrylic acids. These authors confirmed the influence of events taking place in the aqueous phase on the basic mechanisms operating in the particle growth stage.…”
mentioning
confidence: 99%